Pengembangan E-LKPD IPA Berbasis Model Discovery Learning Untuk meningkatkan Hasil Belajar Kognitif pada Materi Perubahan Wujud Zat - Adi Putra Wijaya; Endang Widi Winarni; Neza Agusdianita (UNIB Press, 2026)
The purpose of this study was to develop a DL-based E-LKPD product on the material of changes in the state of matter to improve the cognitive learning outcomes of fourth-grade elementary school students. The type of research used was Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation and evaluation. The data used were quantitative and qualitative data. Quantitative data were obtained from the results of validation by material, language, and graphic experts, product trials, and effectiveness tests through pretests and posttests. Qualitative data were obtained from the results of interviews, observations, and questionnaires of teacher and student responses. The results showed that the DL-based E-LKPD developed according to the material, language, and graphic expert validators was declared suitable for use. Teacher and student responses were categorized as very positive regarding the appearance and ease of use of the media. In addition, the results of the effectiveness test showed an increase in students' problem-solving abilities with an N-Gain Score of 0.7440 which was included in the high category. Based on these results, it can be concluded that the DL-based E-LKPD was effective in improving the cognitive learning outcomes of fourth-grade elementary school students.